2013
DOI: 10.1117/12.2015682
|View full text |Cite
|
Sign up to set email alerts
|

Infrared hyperspectral standoff detection of explosives

Abstract: In this work we demonstrate imaging standoff detection of solid traces of explosives using infrared laser backscattering spectroscopy. Our system relies on active laser illumination in the 7 µm-10 µm spectral range at fully eye-safe power levels. This spectral region comprises many characteristic absorption features of common explosives, and the atmospheric transmission is sufficiently high for stand-off detection. The key component of our system is an external cavity quantum cascade laser with a tuning range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Active QCL illumination coupled with array detectors enables hyperspectral imaging that can match the spectrum of residues with library spectra of explosives ( Fig. 3) [67][68][69][70]. The backscattering collected is a strong function of the angle of incidence, but the contrast in spectral features has been observed to remain with orders of magnitude less signal than specular reflection [64,71].…”
Section: Vibrational and Electronic Spectroscopiesmentioning
confidence: 96%
“…Active QCL illumination coupled with array detectors enables hyperspectral imaging that can match the spectrum of residues with library spectra of explosives ( Fig. 3) [67][68][69][70]. The backscattering collected is a strong function of the angle of incidence, but the contrast in spectral features has been observed to remain with orders of magnitude less signal than specular reflection [64,71].…”
Section: Vibrational and Electronic Spectroscopiesmentioning
confidence: 96%
“…Backscattering images illuminated by the EC-QCL at different wavelengths were recorded here from a close distance of~1 m. Comparison to other samples with known amount of material and visual inspection suggested that the illuminated area contained a total amount of TNT on the order of 100 µg. Previous publications showed that over distances of a few meters, quantitates down to 10 µg are detectable [33]. The backscattering spectrum of jeans denim strongly resembles that of TNT, so false alarms or interferences might be expected.…”
Section: Imaging Mir Laser Backscattering Spectroscopy For the Stand-mentioning
confidence: 97%
“…Instruments can be operated in a "point and shoot" mode using a single pixel detector or in an imaging configuration using a detector array. This second mode has been successfully applied to the detection of solid and liquid contaminants on surfaces 6,7,8 .…”
Section: Current Instrumentationmentioning
confidence: 99%
“…Substituting Equation 4 into Equation 5, the retrieved state appears as a function of the true one as expressed in Equation 6.…”
Section: Generic Approachmentioning
confidence: 99%
See 1 more Smart Citation